2010
DOI: 10.1530/rep-09-0411
|View full text |Cite
|
Sign up to set email alerts
|

A cancer stem cell origin for human endometrial carcinoma?

Abstract: Endometrial cancer (EC) is the most common gynaecological malignancy affecting women in the western world. Cancer stem cells (CSCs) are defined as a subset of tumour cells with the capacity to self-renew and give rise to the differentiated cells that comprise the bulk of the tumour. Given that a rare population of epithelial stem/progenitor cells has been identified in human endometrium, it is possible that these cells or their progeny may be the source of the putative CSCs that may initiate and maintain EC. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 74 publications
0
23
0
1
Order By: Relevance
“…Indeed, since the first evidence for the existence of clonogenic cells in the human endometrium was provided by Chan et al (2004), several studies have reported the presence of a variety of stem-like cells in human and mouse uterus (Chan & Gargett 2006, Cervelló et al 2007, Kato et al 2007, Wolff et al 2007, Dimitrov et al 2008, Gargett et al 2009. Furthermore, emerging evidence indicates that some pathological conditions, such as endometrial cancer, endometriosis, and leiomyomata can be attributed to dysregulation of these same stem cells, or are derived from committed cells that acquire stem-like features (Sasson & Taylor 2008, Hubbard & Gargett 2010. Most studies on uterine stem cells have focused on human rather than mouse models, the latter being the only animal model studied until now.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, since the first evidence for the existence of clonogenic cells in the human endometrium was provided by Chan et al (2004), several studies have reported the presence of a variety of stem-like cells in human and mouse uterus (Chan & Gargett 2006, Cervelló et al 2007, Kato et al 2007, Wolff et al 2007, Dimitrov et al 2008, Gargett et al 2009. Furthermore, emerging evidence indicates that some pathological conditions, such as endometrial cancer, endometriosis, and leiomyomata can be attributed to dysregulation of these same stem cells, or are derived from committed cells that acquire stem-like features (Sasson & Taylor 2008, Hubbard & Gargett 2010. Most studies on uterine stem cells have focused on human rather than mouse models, the latter being the only animal model studied until now.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies in a wide variety of leukemias and solid tumors (AlHajj et al, 2003;Singh et al, 2004;Taylor et al, 2005;Patrawala et al, 2006;Hermann et al, 2007;O'Brien et al, 2007;Ricci-Vitiani et al, 2007;Eramo et al, 2008;Schatton et al, 2008), have followed to identify cell populations with an increased tumor-forming ability as compared to other populations from the same tumor. The interpretation of these and similar results has recently been somewhat complicated by the finding that the tumor formation efficiency of different cell populations can be greatly affected by the host animal, most notably by the level of immunodeficiency in recipient mice (Quintana et al, 2008) (Holland, 2001;Gerdes and Yuspa, 2005;Shupe and Petersen, 2005;Hubbard and Gargett, 2010;Sell, 2010;Waters et al, 2010;Visvader, 2011) (Jögi et al, 2002;Helczynska et al, 2003), or occur as a natural consequence of tumor progression (Delahunt, 1999), long before the cancer stem cell model regained mainstream interest in the research community.…”
Section: B the Cancer Stem Cell Modelmentioning
confidence: 98%
“…that equally affect all cells within a tumor [47]. The hierarchal model, on the other hand, holds that particular cells within a lineage are susceptible to transformation, and these self-renewing cells give rise to heterogeneous progeny [48, 49]. The cells at the pinnacle of the hierarchy can initiate de novo tumors and may account for resistance of cancer to chemotherapy and radiation [48, 49] (Fig.…”
Section: Stem-like Basis For Human Malignanciesmentioning
confidence: 99%
“…These cells are expected to self-renew and give rise to new tumors limitlessly [48, 49]. The pluripotency marker Oct-4 is shown here as a potential marker of these cancer-initiating cells…”
Section: Figmentioning
confidence: 99%